Swallowing Disorders - Rodríguez Menéndez, Abelardo Emilio (2022)
Objective: Updating of knowledge related to the swallowing process and its disorders, and to encourage reflection among health professionals. Material and methods: A bibliographic review of 60 international authors, from which 27 works were selected on the swallowing process and its disorders, in order to update and group up-to-date knowledge on anatomy, physiology, pathophysiology, clinical picture, semiotechnics and techniques study. Development: An anatomical and physiological count, pathophysiology, clinical picture and main investigations that are carried out for the diagnosis of swallowing disorders are shown. Conclusion: The health professional will be able to delve into basic clinical aspects related to the swallowing process and expand their knowledge about disorders related to this process, in this way they will be able to recognize dysphagia in patients as a symptom and make a correct referral for evaluation.